2000
DOI: 10.1182/blood.v96.6.2012.h8002012a_2012_2021
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of hematopoietic progenitor/stem cells in 5q-deleted myelodysplastic syndromes: evidence for involvement at the hematopoietic stem cell level

Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of clonal disorders characterized by ineffective hematopoiesis and frequent progression to acute myeloid leukemia. Within MDS, 5q− syndrome constitutes a distinct clinical entity characterized by an isolated deletion of the long arm of chromosome 5 (5q−), a relatively good prognosis, and infrequent transformation to acute leukemia. The cell of origin in 5q− syndrome as well as in other 5q-deleted MDS patients has not been established, but evidence for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 57 publications
8
68
0
3
Order By: Relevance
“…Hypermethylation of promoter CpG islands could be detected in both immunoseparated CD34 + precursor cells and total BM‐MNC, and the methylation band patterns in these sample types were similar. Together with a previous study showing that p15 INK 4 B hypermethylation is not restricted to blast cells but to cells from the MDS clone in general (23), these observations suggest that promoter hypermethylation encompasses both immature and end‐stage hematopoietic cells and provide independent support for the contention that MDS is essentially a stem cell disorder (24). As hypomethylating agents are being increasingly used in clinical trials of treatment for MDS (25, 26), it may be helpful to know that clinical monitoring of promoter methylation status can be reliably accomplished directly on unseparated BM‐MNC with no need for purification of CD34 + precursor cells.…”
Section: Discussionsupporting
confidence: 74%
“…Hypermethylation of promoter CpG islands could be detected in both immunoseparated CD34 + precursor cells and total BM‐MNC, and the methylation band patterns in these sample types were similar. Together with a previous study showing that p15 INK 4 B hypermethylation is not restricted to blast cells but to cells from the MDS clone in general (23), these observations suggest that promoter hypermethylation encompasses both immature and end‐stage hematopoietic cells and provide independent support for the contention that MDS is essentially a stem cell disorder (24). As hypomethylating agents are being increasingly used in clinical trials of treatment for MDS (25, 26), it may be helpful to know that clinical monitoring of promoter methylation status can be reliably accomplished directly on unseparated BM‐MNC with no need for purification of CD34 + precursor cells.…”
Section: Discussionsupporting
confidence: 74%
“…In both disorders cytogenetic and FISH studies aimed at establishing whether mesenchymal stromal cells (MSC) harbour the same cytogenetic abnormalities of the neoplastic clone have provided conflicting results (Soenen‐Cornu et al , 2005; Blau et al , 2007). In contrast to leukemic cells, propagation of MDS‐derived clones in vitro or in vivo has proven difficult (Nilsson et al , 2000; Benito et al, 2003). In vitro studies have revealed difficulties in establishing stromal layers from MDS bone marrow mononuclear cells (BMNC) (Manakova et al , 2000; Tennant et al , 2000) and these adherent stromal layers show an abnormal interleukin (IL) 1β expression (Tennant et al , 2000).…”
Section: Role Of the Microenvironmentmentioning
confidence: 99%
“…MDS is a disease of the stem cells. It was already shown two decades ago that cytogenetic abnormalities found in mature myeloid cells are also found in stem cells . Recent work has shown that different mutations can also be found within the stem cell compartment .…”
Section: Pathogenesismentioning
confidence: 99%